Fast-Food Industry Company in the context of pandemic COVID-19: Case of KFC on Spanish Market - Elena V. KOLGANOVA; Dmitry I. BABIY; Alexander I. BABIY (Communications of International Proceedings, 2020)
The pandemic COVID-19 has a great impact on different spheres of life in countries all over the world. In the current article the authors presented the results of the research devoted to the analysis of the fast-food company activity in Spain. KFC was chosen as an object of the research. This theme is very interesting and actual as the out-of-home dining culture is highly developed in Spain. At the same time, fast-food is not preferred by the Spaniards. They choose more healthy food and in case of fast-food they would prefer Spanish cafeteria instead of world-famous brand. That is why the authors suggested that the KFC company can suffer much more from the COVID-19 pandemic and lockdown and made various analyses to define the real situation.
Keywords: Pandemic COVID-19; Spain; Food Industry; Fast-Food Company; KFC